Manual of Tests and Criteria - Seventh Revised Edition - United Nations Economic Commission for Europe (United Nations, 2019)
The Manual of Tests and Criteria contains criteria, test methods and procedures to be used for classification of dangerous goods according to the provisions of Parts 2 and 3 of the United Nations Recommendations on the Transport of Dangerous Goods, Model Regulations, as well as of chemicals presenting physical hazards according to the Globally Harmonized System of Classification and Labelling of Chemicals (GHS). As a consequence, it supplements also national or international regulations which are derived from the United Nations Recommendations on the Transport of Dangerous Goods or the GHS. At its ninth session (7 December 2018), the Committee adopted a set of amendments to the sixth revised edition of the Manual as amended by Amendment 1. This seventh revised edition takes account of these amendments. In addition, noting that the work to facilitate the use of the Manual in the context of the GHS had been completed, the Committee considered that the reference to the “Recommendations on the Transport of Dangerous Goods” in the title of the Manual was no longer appropriate, and decided that from now on, the Manual should be entitled “Manual of Tests and Criteria